CD4 T cells target colorectal cancer antigens upregulated by oxaliplatin. Issue 11 (31st August 2019) - Galaine, Jeanne; Turco, Célia; Vauchy, Charline; Royer, Bernard; Mercier‐Letondal, Patricia; Queiroz, Lise; Loyon, Romain; Mouget, Virginie; Boidot, Romain; Laheurte, Caroline; Lakkis, Zaher; Jary, Marine; et al.
Abstract : Immune checkpoint blockade has proven its efficacy in hypermutated subtypes of metastatic colorectal cancers (mCRC). Immunogenic potential can also be observed with conventional chemotherapies, but this property has never been explored thoroughly in CRC patients. The CRC therapeutic arsenal includes oxaliplatin, a well‐characterized platinum drug already described as immunogenic. Here, we investigated the impact of the oxaliplatin‐based treatment on mCRC immunopeptidome. We demonstrated that oxaliplatin‐resistant CRC cell lines overexpressed telomerase reverse transcriptase (TERT), colorectal‐associated‐tumor antigen‐1 (COA‐1) and mesothelin tumor‐associated antigens. We identified new HLA class‐II‐restricted and promiscuous peptides derived from COA‐1 and mesothelin. The two naturally processed peptides COA‐1331‐345 and Meso366‐380 appear to be the most immunogenic in mCRC patients. A prospective cohort of 162 mCRC patients enabled us to explore the impact of oxaliplatin exposure on the antitumor‐specific immune response. Interestingly, chemotherapy‐naive mCRC patients present high immune CD4 T‐cell responses directed against TERT, COA‐1 and mesothelin‐derived peptides. These antitumor T‐cell responses were maintained after 3 months of oxaliplatin‐based treatment. Altogether, these findings highlight the interest of immunostimulatory agents to improve the management of chemoresistant mCRC patients. Finally, the high frequency of immune responses targeting the new immunogenic peptides derived from COA‐1 and mesothelin support their use in immunomonitoring strategies. Abstract : What's new? Oxaliplatin, like other platinum drugs, kills cancer cells through induction of DNA damage, but immunomodulatory properties have also been described. Here the authors examined the immunopeptidome in oxaliplatin‐resistant colon cancer cell lines. They identified novel MHC class II‐restricted peptides derived from overexpressed tumor antigens and show that these are immunogenic in metastatic colorectal cancer patients treated with oxaliplatin. These findings may lead to new immunotherapeutic approaches to oxaliplatin‐resistant colon cancer.